2015
DOI: 10.1002/ddr.21249
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic Effects of Gambogic Acid are Mediated via the Actin Cytoskeleton and NF‐κB Pathways in SKHEP1 Cells

Abstract: Hepatocellular carcinoma (HCC) is one of the most malignant and frequent cancers with a high metastatic potential. The prevention of HCC metastasis is a critical target for effective therapies in HCC. Gambogic acid (GA), a natural compound obtained from Garcinia hanburyi has reported anticancer activity in cell lines. However, the antimetastatic mechanisms of GA are unclear, particularly with respect to HCC. In this study, the influence of GA on migration and invasion of SK-HEP1 cells was evaluated. At concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…SK-Hep1 is an immortal, human cell line derived from the ascetic fluid of a patient with liver adenocarcinoma. High metastatic capacities of SK-Hep1 cells are suitable for cancer metastasis research and have been used wildly in the literature (Park et al 2015 ). In this study we examined the antimetastatic effects of EAAC in human hepatoma SK-Hep1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…SK-Hep1 is an immortal, human cell line derived from the ascetic fluid of a patient with liver adenocarcinoma. High metastatic capacities of SK-Hep1 cells are suitable for cancer metastasis research and have been used wildly in the literature (Park et al 2015 ). In this study we examined the antimetastatic effects of EAAC in human hepatoma SK-Hep1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that treatment with gambogic acid significantly inhibited MMP-2 and MMP-9 protein expression in cardiac tissues of AMI rats. Park et al (14) suggested that gambogic acid decreased MMP-2, MMP-9 and NF-κB expression in SK-HEP1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tumor effects of gambogic acid are extensive and include the induction of tumor cell apoptosis, inhibition of the cell cycle, and an influence on the expression of certain oncogenes, cancer suppressor genes and associated proteins (13). As an anti-tumor drug, gambogic acid has an obvious inhibitory effect on the growth of tumors grown in animal models, but anti-tumor drugs often generate untoward effects and easily cause irreversible damage to the hemopoietic and immune system (14). In the present study, a rat model of AMI was used to investigate the protective effects of gambogic acid and their possible association with inhibition of inflammation via the iNOS and nuclear factor (NF)-κB/p38 pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, both in vitro and in vivo evidence revealed the potent anti-tumor efficacies of GA, not only in solid tumors Ishaq et al, 2014;Zhao et al, 2008;Park et al, 2015), but also in hematological malignancies (Gupta et al, 2010;Prasad et al, 2011;Yang and Chen, 2013). However, the anti-tumor efficacies of GA in B-cell NHL and the underlying mechanism have not been fully uncovered.…”
Section: Introductionmentioning
confidence: 97%